2018
DOI: 10.18203/issn.2455-4510.intjresorthop20182020
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial comparing the intra-articular hyaluronic acid versus intra-articular steroid in osteoarthritis of knee

Abstract: <p class="abstract"><strong>Background:</strong> Osteoarthritis of knee is a chronic degenerative joint disease which leads to pain, swelling and stiffness. Intra-articular hyaluronic acid or steroids are being used for its treatment. The purpose of the present study was to assess the effect of intra articular hyaluronic acid in comparison to steroids for knee osteoarthritis.</p><p class="abstract"><strong>Methods:</strong> A prospective randomized study including 70 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…During the first month of post injection, the steroid group had better improvement in scores as compared to Hyaluronic acid group. 11 We also found similar effect at 1 week in our study but in long term at 6 months follow up, they found that the results were better with Hyaluronic acid. Similar effect showed in combination therapy in the 3rd month in our study.…”
Section: Discussionsupporting
confidence: 86%
“…During the first month of post injection, the steroid group had better improvement in scores as compared to Hyaluronic acid group. 11 We also found similar effect at 1 week in our study but in long term at 6 months follow up, they found that the results were better with Hyaluronic acid. Similar effect showed in combination therapy in the 3rd month in our study.…”
Section: Discussionsupporting
confidence: 86%